THE EPISTOLARY IMAGE OF T. SHEVCHENKO: A SYMBOLIC APPROACH - Ilkiv , Anna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the role of folk images-symbols in the textual organization of T. Shevchenko’s letters. The writer’s intensity of the epistolary is investigated through decodisation of the main concepts and symbols of epistolary writing and associative text chains.